Dinamika Psikologis Perilaku Self-Harm pada Mahasiswa Tingkat Akhir Program Studi Bimbingan Konseling: Psychological Dynamics of Self-Harm Behavior in Final Students of Guidance and Counseling Study Program - Hafid, Istiqamah; Usop, Dwi Sari (Anterior Jurnal, 2025)
Self-harm is a behavior of deliberately inflicting injury upon oneself, driven by overwhelming pressure. Uncontrollable stress can lead to fatal consequences, including death. Final-year university students are among the individuals vulnerable to self-harm, often due to the pressure to graduate promptly. Furthermore, self-harm can be triggered by factors such as gender, feelings of loneliness, abandonment by loved ones, strained family relationships, and discrepancies between expectations and realities regarding lifestyle and economic conditions. This study aims to describe the psychological dynamics of final-year university students who have experienced self-harm. Employing a descriptive qualitative research methodology, the study involved three subjects: final-year students from the Guidance and Counseling study program who had engaged in self-harm within the past four years. Data collection techniques included observation, interviews, and documentation. The research findings revealed the following: Parental influence plays a significant role in the occurrence of self-harm through acts of physical violence inflicted upon the subjects (A, B, C); Self-harm was triggered in all three subjects by conflicts with parents, friends, or romantic partners; The forms of self-harm exhibited included the consumption of generic drugs, ranging from one to three pills, inducing prolonged sleep, social withdrawal, head-banging against walls, hair-pulling, self-hitting, scratching, and biting of body parts.